Diverse pathways to neuronal necroptosis in Alzheimer's disease - Jayaraman, Anusha (2022)
Necroptosis, or programmed necrosis, involves the kinase activity of receptor interacting kinases 1 and 3, the activation of the pseudokinase mixed lineage kinase domain-like and formation of a complex called the necrosome. It is one of the non-apoptotic cell death pathways that has gained interest in the recent years, especially as a neuronal cell death pathway occurring in Alzheimer's disease. In this review, we focus our discussion on the various molecular mechanisms that could trigger neuronal death through necroptosis and have been shown to play a role in Alzheimer's disease pathogenesis and neuroinflammation. We describe how each of these pathways, such as tumour necrosis factor signalling, reactive oxygen species, endosomal sorting complex, post-translational modifications and certain individual molecules, is dysregulated or activated in Alzheimer's disease, and how this dysregulation/activation could trigger necroptosis. At the cellular level, many of these molecular mechanisms and pathways may act in parallel to synergize with each other or inhibit one another, and changes in the balance between them may determine different cellular vulnerabilities at different disease stages. However, from a therapeutic standpoint, it remains unclear how best to target one or more of these pathways, given that such diverse pathways could all contribute to necroptotic cell death in Alzheimer's disease.